Burn‐Induced Gut Microbiota Dysbiosis Aggravates Skeletal Muscle Atrophy by Tryptophan‐Kynurenine Mediated AHR Pathway Activation - Shan Gao; Yan Leng; Zhen Qiu; Kai Li; Jun Li; Jian Peng; Weiguo Xie; Shaoqing Lei; Zhongyuan Xia (Advanced Science)
Abstract The hypermetabolic response associated with burns is characterized by skeletal muscle atrophy and an increased incidence of disability and death. Significant remodeling of the gut microbiota occurs after severe burn trauma. However, the specific mechanisms by which gut microbiota contribute to burn‐induced muscle atrophy remain unexplored. The results showed that the disruption of the gut microbiota exacerbated skeletal muscle atrophy. Fecal metabolite analysis revealed perturbations, primarily within the tryptophan (Trp) metabolic pathway. Animal models further demonstrated that gut microbiota disorder enhanced the expression of indoleamine 2,3‐dioxygenase 1 (IDO‐1) in the colon, ultimately resulting in Trp depletion and increased kynurenine (Kyn) levels in the serum and skeletal muscle. Excessive colonic Kyn is released into circulation, transported into skeletal muscle cells, and binds to the aryl hydrocarbon receptor (AHR), consequently triggering AHR nuclear translocation and initiating the transcription of skeletal muscle atrophy‐related genes. Notably, serum samples from patients with burns exhibited Trp depletion, and Trp supplementation alleviated skeletal muscle atrophy in rats with burns. This study, for the first time, demonstrates that gut microbiota dysbiosis upregulates colonic IDO‐1, promotes Trp‐Kyn metabolism, and exacerbates burn‐induced skeletal muscle atrophy, suggesting that Trp supplementation may be a potential therapeutic strategy.